AN EXPERIENCE OF USING SIMVASTATINUM IN THE METABOLIC SYNDROME OF PATIENTS WITH CHRONIC CHOLECYSTITIS AND DIABETES MELLITUS TYPE II - Vovk, K.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The combined pathology of the internal organs at present time is the issue of the day in therapy. The aim of the work: to define the influence of simvastatinum on the index of the lipid spectrum of the blood serum of patients with chronic cholecystitis (CC) and diabetes mellitus (DM) type II. The patients with CC and DM type II, in comparison with patients only with CC, have dislipidemia, which is characterized by: hypercholesterolemia, hypertriglyceridemia, increase of the low density and very low density lipoprotein cholesterol index, and the reduction of the high density lipoprotein cholesterol index. The treatment of patients with both, CC and DM type II, using simvastatinum in doses of 20 mg/day result the normalization of the lipid spectrum of blood serum indexes, and may be used both as prophylaxis of the metabolic syndrome, and as treatment of patients of this category.